The roles of different Bacteroides fragilis strains in protecting against DSS-induced ulcerative colitis and related functional genes. Issue 18 (26th July 2021) - Wang, Chen; Li, Sijia; Hong, Kan; Yu, Leilei; Tian, Fengwei; Zhao, Jianxin; Zhang, Hao; Chen, Wei; Zhai, Qixiao
Abstract : The role of supplementation with different Bacteroides fragilis ( B. fragilis ) strains in alleviating ulcerative colitis (UC) is unclear due to the controversial results from animal experiments. Abstract : The role of supplementation with different Bacteroides fragilis ( B. fragilis ) strains in alleviating ulcerative colitis (UC) is unclear due to the controversial results from animal experiments. In this study, three B. fragilis strains were evaluated for their ability to alleviate dextran sulfate sodium (DSS)-induced UC in C57BL/6J mice. We analyzed the anti-inflammatory effects of different B. fragilis strains and the changes they caused in the intestinal microbiota composition, intestinal epithelial permeability, cytokine concentrations, protein expression of nuclear factor kappa-B (NF-κB) and the underlying specific genes. The results showed that when orally administered, the different B. fragilis strains exerted different effects on the assessed parameters of the mice. The results of real-time quantitative polymerase chain reaction and immunofluorescence staining showed that the supplementation of B. fragilis FSHCM14E1, but not FJSWX11BF, enhanced the expression of the tight-junction proteins ZO-1, occludin and claudin-1. Western blot analysis showed that the anti-inflammatory effects of B. fragilis FSHCM14E1 were related to the NF-κB pathway. Genomic analysis suggested that the anti-inflammatory effects of FSHCM14E1 may be mediated through specific genes associated with defense mechanisms and the secretion of SCFAs. Overall, this study indicates the therapeutic potential of B. fragilis FSHCM14E1 for the prevention of UC.